Specific Subjective Symptoms for Gastroesophageal Reflux Disease in Ulcer Like Dyspepsia - Poerniati Koes Andrijani; Chudahman Manan; Marcellus Simadibrata; Parlindungan Siregar (The Indonesian Society for Digestive Endoscopy, 2004)
Background: The Aim of study is to identify specific subjective symptoms for gastroesophageal reflux disease (GERD), GERD proportion in ulcer like dyspepsia and the correlation between specific subjective symptoms for GERD and endoscopic examination Result in ulcer like dyspepsia Methods: A cross-sectional study was conducted in 67 patients with ulcer like dyspepsia. The patient’s history of illness was taken, and physical and endoscopic examinations were performed. A questionnaire on dyspepsia symptoms was completed. Data analysis was performed to identify the correlation between subjective symptoms and endoscopic examination results using chi-square test. T test was performed to determine the correlation between dyspepsia scores and endoscopic results. Result: Subjective symptoms that correlated with endoscopic results were severe epigastric pain (p=0.080) and the absence of bloating (p=0.055). Dyspepsia scores did not correlate with endoscopic examination results (p=0.725). Conclusion: Specific subjective symptoms for GERD in clinical dyspepsia-like ulcer were severe epigastric pain and absence of bloating. The proportion of such symptoms in ulcer like dyspepsia could assist clinical diagnosis of GERD. Keywords: GERD, symptom, dyspepsia